Peripheral Refraction in Myopic Children with and without Atropine Usage - Han-Yin Sun; Wei-Yang Lu; Jhen-Yu You; Hui-Ying Kuo (Journal of Ophthalmology)
Purpose. To compare the patterns of relative peripheral refractions of myopic children who were currently on atropine treatment for myopia control and myopic children who did not use atropine. Methods. Chinese children (n = 209) aged 7 to 12 years participated in the study, 106 used atropine and 103 did not. Participants were also classified into three groups: emmetropes (SE: +0.50 to −0.50 D), low myopes (SE: −0.50 to −3.00 D), and moderate myopes (SE: −3.00 to −6.00 D). The central and peripheral refractions along the horizontal meridians (for both nasal and temporal fields) were measured in 10-degree steps to 30 degrees. Results. There were no statistically significant differences in spherical equivalent and astigmatism of the three refractive groups in either the nasal or temporal retina. The atropine group showed a significant relative myopia in the temporal 30° field in spherical equivalent compared to the emmetropic group (t49 = 3.36, P=0.02). In eyes with low myopia, the atropine group had significant relative myopia in the nasal 30° and temporal 30° fields (t118 = 2.59, P=0.01; t118 = 2.06, P=0.04), and it is also observed at 20° and 30° of the nasal field for the moderate myopic group (t36 = 2.37, P=0.02; t2.84 = 2.84, P=0.01). Conclusion. Significant differences in relative peripheral refraction were found between the atropine group and its controls. The findings suggested that the eyes that received atropine may have a less prolate shape and thus explain why using atropine is effective in controlling myopia progression.